Penentuan Titik Pengambilan Objek Secara Otomatis Untuk Asisten Robot Ahli Bedah Pada Sistem KNN - Aini, Fica Aida Nadhifatul; Monasari, Ratna; Puspitasari, Etik; Amalia, Zakiyah; Machfuroh, Talifatim; N. R., Siti Duratun (ROTASI, 2024)
Technological developments will gradually be able to replace the role of human work. One of the most interesting primary functions of humans is the eye. Object recognition is the main point in technology to identify objects in images or videos. This research implements surgical tool detection to determine the retrieval point on the robotic arm. The surgical tool detection method used is to separate the object from the background using the OpenCV library. First, convert the image to HSV (Hue Saturation Value). Second, look for the threshold of the HSV image which has been separated by channels. This is done to obtain sharp image contrast. Next, contour detection for each object. The retrieval points are obtained from moment calculations by contour. The experimental results showed that the center point could be detected well even if the position of the surgical tool was changed.